Outdoor particulate matter and childhood asthma admissions in Athens, Greece: A time-series study - Nastos, P. T.; Paliatsos, A. G.; Anthracopoulos, M. B.; Roma, E. S.; Priftis, K. N. (Environmental Health: A Global Access Science Source, 2010)
Background: Particulate matter with diameter less than 10 micrometers (PM10) that originates from anthropogenic activities and natural sources may settle in the bronchi and cause adverse effects possibly via oxidative stress in susceptible individuals, such as asthmatic children. This study aimed to investigate the effect of outdoor PM10concentrations on childhood asthma admissions (CAA) in Athens, Greece. Methods: Daily counts of CAA from the three Children's Hospitals within the greater Athens' area were obtained from the hospital records during a four-year period (2001-2004, n = 3602 children). Mean daily PM10concentrations recorded by the air pollution-monitoring network of the greater Athens area were also collected. The relationship between CAA and PM10concentrations was investigated using the Generalized Linear Models with Poisson distribution and logistic analysis. Results: There was a statistically significant (95% CL) relationship between CAA and mean daily PM10concentrations on the day of exposure (+3.8% for 10 μg/m3 increase in PM10concentrations), while a 1-day lag (+3.4% for 10 μg/m3 increase in PM 10concentrations) and a 4-day lag (+4.3% for 10 g/m3 increase in PM10concentrations) were observed for older asthmatic children (5-14 year-old). High mean daily PM10concentration (the highest 10%; >65.69 μg/m3) doubled the risk of asthma exacerbations even in younger asthmatic children (0-4 year-old). Conclusions: Our results provide evidence of the adverse effect of PM10on the rates of paediatric asthma exacerbations and hospital admissions. A four-day lag effect between PM10peak exposure and asthma admissions was also observed in the older age group. © 2010 Nastos et al; licensee BioMed Central Ltd.
Keywords: Adolescent; air pollutant; Air Pollutants; Air pollution; anthropogenic effect; article; asthma; Athens [Attica]; atmospheric pollution; Attica; chemically induced disorder; Child; child health; Child, Preschool; childhood disease; cohort analysis; disease exacerbation; environmental exposure; Female; Greece; health risk; hospital admission; Hospitalization; human; Humans; Infant; Infant, Newborn; Linear Models; Logistic Models; major clinical study; Male; medical record; Newborn; oxidation; Particulate matter; preschool child; priority journal; school child; seasonal variation; statistical model; Statistics; time; Time Factors; time series